2018
DOI: 10.1007/s13337-018-0484-y
|View full text |Cite
|
Sign up to set email alerts
|

Differentially expressed serum host proteins in hepatitis B and C viral infections

Abstract: Hepatitis B virus (HBV) and Hepatitis C virus (HCV) infection often lead to hepatocellular carcinoma (HCC), which is mostly detected in advanced stage. Hence, its early detection is of paramount importance using a biomarker having sensitivity and specificity both. The present study highlights differentially expressed host proteins in response to HBV/HCV infection at different stages. Comparative proteomic study was done by two-dimensional gel electrophoresis followed by mass spectrometry. Sera from each of ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…Most of the literature about systematic -omics studies made in the scales of genomics, transcriptomics and proteomics in the HCV and HCV field are, in fact, related to HCC susceptibility, which is a priority topic for research 6 , 7 . Other studies comparatively analyzed different stages of chronic liver damage in HCV and HBV infections, always with the aim to find early cancer biomarkers using proteomics 8 , 9 .…”
Section: Introductionmentioning
confidence: 99%
“…Most of the literature about systematic -omics studies made in the scales of genomics, transcriptomics and proteomics in the HCV and HCV field are, in fact, related to HCC susceptibility, which is a priority topic for research 6 , 7 . Other studies comparatively analyzed different stages of chronic liver damage in HCV and HBV infections, always with the aim to find early cancer biomarkers using proteomics 8 , 9 .…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13] Low serum ceruloplasmins have also been described in patients without WD with chronic liver disease. 12,14,15 When present, this finding will often result in extensive, costly, and potentially harmful additional investigations. Thus, the objectives of this study were to document the prevalence of low serum ceruloplasmin levels in adult patients without WD attending a large urban liver diseases outpatient program and determine whether certain clinical and/or biochemical features help to identify when non-WD hypoceruloplasminemia is more likely to be present in this patient population.…”
mentioning
confidence: 99%
“…It is a liverinduced glycoprotein enzyme responsible for protection against reactive oxygen species and inflammation and has been associated with various cancers. PON1 may also be a risk factor for chronic hepatitis B [17], and glycan differences in serum PON1 may serve as potential biomarkers to distinguish early HCC from liver cirrhosis [18]. In this study, we have shown that PON1 expression was significantly decreased in HCC using iTRAQ-based serum proteomic analysis.…”
Section: Discussionmentioning
confidence: 62%